Using industrial ecology and strategic management concepts to pursue the Sustainable Development Goals. (10th February 2018) - Sullivan, Kieran; Thomas, Sebastian; Rosano, Michele
Abstract: The subjectivity, complexity, and often competing interests of sustainable development have limited the effectiveness of integrating these important ideas into mainstream business strategy. With the adoption of the UN Sustainable Development Goals (SDGs) in January 2016, there are now global sustainability benchmarks that apply across diverse sectors and national contexts, allowing public and private organizations to orient and evaluate their activities, strategies, and business outcomes. However, it is not directly apparent where the advantage for business lies in pursuit of these actions within the prevailing economic paradigm, highlighting the need for new analytical frameworks and tools. Industrial ecology (IE) has been successfully used in engineering practice for decades and has been suggested as a method that can provide the concepts and methods necessary to bridge the gap between traditional business practice and sustainable development. To test this, literature bridging the fields of industrial ecology, business strategy, and sustainable development was collected and analyzed using the textual analysis software Leximancer™. The analysis showed that while the SDGs are primarily aimed at the national level, they also hold relevance for business through innovation, partnerships, and strategic positioning, inter alia. The analysis found that the integration of IE and business strategy is highly relevant for three of the SDGs, but captures elements of all 17 to varying degrees. IE has a strong focus on innovation and its potential in new markets, products, and business models. IE is also consciously aimed at the efficient use of energy and resources, ideas that are relevant to mitigating, adapting, and building resilience in a changing future, but are also relevant to traditional concepts of business strategy and competitive advantage. This paper shows that through the combination of IE and strategic management theory, commercial organizations can positively contribute to the Sustainable Development Goals while building competitive advantage. Highlights: Systematic review of literature with a thematic and conceptual analysis using Leximancer™. Industrial ecology principles are shown to lead to competitive advantage in line with Sustainable Development Goals. The study establishes a baseline for quantitative analysis of the strategic benefits of IE principles.